Mentoring and Empowerment Diploma Three Student in Blood Bank Technology, Health Polytechnic, Ministry of Health, Semarang, Through Training in Making Soy Milk as an Effort to Prevent Anemia - Afrianti, Dina; Hartono, Rodhi; Setyowatiningsih, Lilik; Sofyanita, Eko Naning; Wahyudi (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
Mentoring participants know about anemia and its symptoms. Participants know the equipment and materials needed to make soy milk and know the steps on how to make soy milk and participants are able to give a demonstration of making soy milk to the residents of the target village. Residents of the assisted villages know how to make soy milk. Community service activities with the Entrepreneurship Development Program (PPK) scheme with the theme "Assistance in the Empowerment of Diploma Three Technology Students at the PolkesMar Blood Bank through training in making soy milk (Soymilk) as an effort to prevent anemia" was carried out on Friday 28 July 2023 with a target of 10 people participating. consisting of 8 active students and 2 alumni. The output is in the form of videos and pamphlets on making soy milk that have received IPR certificates as well as the expertise of training participants resulting from a series of training activities on making soy milk (Soymilk) targeting students and alumni. This has also been implemented in community service activities for the target village residents in Pundan Hamlet, Subdistrict. Kebondowo Banyubiru, Semarang district, which will be held on Sunday 15 October 2023. The successful achievement of this activity was that all participants in the training on making soy milk were able to give demonstrations on making soy milk to the residents of the target villages. Residents of the assisted villages were given education about anemia and solutions to preventing anemia, the committee also showed videos of making soy milk, distributed pamphlets and gifts to residents of the assisted villages.